Beta-Lactamases Produced by a Pseudomonas aeruginosa Strain Highly Resistant to Carbenicillin - Labia, Roger (1977)
A Pseudomonas aeruginosa strain isolated at Besançon Hospital, France, proved to be highly resistant to carbenicillin and showed a high hydrolytic activity toward this antibiotic. We clearly demonstrated that two β-lactamases were synthetized: one of them, constitutive, has its enzymatic activity directed mainly toward penicillins, and carbenicillin appears to be its best substrate (higher V(max)); thus, this β-lactamase is a “carbenicillinase” that differs from the well-known “TEM-like” enzymes. The isoelectric point of this carbenicillinase is 5.30 ± 0.03. The other one is an inducible cephalosporinase, very similar to the cephalosporinases usually found in these organisms. Its isoelectric point is 8.66 ± 0.04. These two enzymes have been separated by affinity chromatography and isoelectric focusing. The kinetic constants were measured by computerized microacidimetry.